A distant magmatic source for Cretaceous karst bauxites of Southern Apennines (Italy), revealed through SHRIMP zircon age dating - Boni, Maria; Reddy, Steven; Mondillo, Nicola; Balassone, Giuseppina; Taylor, Rich (Blackwell Publishing Ltd, 2012)
Karst bauxites occur at a Late Cretaceous hiatus on a Bahamian-type platform in Southern Apennines, Italy. In contrast to the well-defined stratigraphic context, their origin remains controversial. Detrital zircon grains preserve textures and Th/U ratios consistent with crystallization from a melt, occasionally around older cores. U-Pb isotopic data, collected using SHRIMP II, record several age populations. The youngest (~90 Ma) falls into the age interval of bauxite formation as defined by stratigraphic criteria. The zircons must therefore be derived from a contemporary Cretaceous volcanic source. The older zircons may be interpreted as xenocrysts associated with the Cretaceous magmas or derived from different sources. Because the bauxite occurs on a isolated carbonate platform, the grains must come from far away sources, most probably transported by wind. The age, palaeogeography and inferred Cretaceous wind pattern are consistent with a prevailing origin from the Dinaric and Carpatho-Balkan orogenic belts, with its Cretaceous bimodal volcanism.